IMPLEMENTASI PERANGKAT PEMBELAJARAN BIOLOGI BERORIENTASI INQUIRY UNTUK MENINGKATKAN KREATIVITAS SISWA - Masiah Masiah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2019)
The purpose of this study is to see the practicality and effectiveness of the learning tools that have been developed so as to enhance students' creative ideas. This type of research is pre-experimental research design with one group pre-test village post-test. The instrument in this study was the observation sheet of the implementation of learning, student questionnaire responses and tests of creative thinking skills. The data obtained were analyzed descriptively quantitatively. The results showed that students' responses to the learning process by using inquiry-oriented learning tools in general students felt interested and the results of thinking ability tests showed a classical completion. Based on these results it can be concluded that the implementation of inquiry-oriented learning tools can be declared practical and effective to improve students' creative ideas.